Malocclusion with posterior unilateral crossbite affects superficial masseter and anterior temporal muscle activity during mastication - Yona Pricilia Anggi Siregar; C. Christnawati; Darmawan Soetantyo (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: Mastication patterns due to malocclusion with unilateral posterior crossbite may permanently change. Purpose: This study aimed to examine the effect of malocclusion with unilateral posterior crossbite of the superficial masseter and anterior temporal muscles on the crossbite and non-crossbite sides during mastication. Methods: Thirty subjects (8 males and 22 females) between the ages of 17 and 30 years who were students of the 2017–2019 Dentistry and Dental Hygiene Study Program, Faculty of Dentistry, UGM and who had at least two posterior teeth with unilateral posterior crossbite were divided into 10 subjects with Angle’s class I, 10 subjects with class II and 10 subjects with class III malocclusions. The amplitude of the superficial masseter and temporal anterior muscles was performed during mastication using surface electromyography (sEMG). The mean difference between the groups of malocclusion on the crossbite and non-crossbite sides of the superficial masseter and temporal anterior was analysed by a two-way analysis of variance (ANOVA). Results: The results indicated a difference in amplitude mean between the malocclusion types on the crossbite sides and non-crossbite sides of the superficial masseter and temporal anterior muscles (p<0.05). This study confirmed there was a decrease in superficial masseter and anterior temporal muscle activity on the crossbite side rather than in the non-crossbite side in Angle’s class I and class II. However, there was an increase in activity of the superficial masseter and anterior temporal muscles on the crossbite side for class III. Conclusion: Malocclusion with unilateral posterior crossbite affects masticatory activity of the superficial masseter and temporal anterior muscles on the crossbite side.